2019
DOI: 10.3390/nu11123040
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mushroom Extracts on Human Platelet and Blood Coagulation: In vitro Screening of Eight Edible Species

Abstract: Cardiovascular diseases remain the leading global cause of mortality indicating the need to identify all possible factors reducing primary and secondary risk. This study screened the in vitro antiplatelet and anticoagulant activities of hot water extracts of eight edible mushroom species (Agaricus bisporus, Auricularia auricularia-judae, Coprinus comatus, Ganoderma lucidum, Hericium erinaceus, Lentinula edodes, Pleurotus eryngii, and Pleurotus ostreatus) increasingly cultivated for human consumption, and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…At the beginning of the present study, we clearly demonstrated that the aqueous extract of AR had significant antioxidative activity in DPPH and TAC assays. In good agreement with the higher phenolic content of AR, the antioxidant capacity of AR extract was also stronger than that reported for aqueous extract of Ganoderma lucidum [ 26 ]. The antioxidant effect of AR extract was further examined in an in vitro model of Parkinson's disease, with PC12 cells.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At the beginning of the present study, we clearly demonstrated that the aqueous extract of AR had significant antioxidative activity in DPPH and TAC assays. In good agreement with the higher phenolic content of AR, the antioxidant capacity of AR extract was also stronger than that reported for aqueous extract of Ganoderma lucidum [ 26 ]. The antioxidant effect of AR extract was further examined in an in vitro model of Parkinson's disease, with PC12 cells.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the results of chemical assays demonstrated that the aqueous extract of AR contained phenolic compounds, polysaccharides, and triterpenes. The contents of total polysaccharides and triterpenes of AR extract were lower than that of aqueous extract of Ganoderma lucidum [ 26 , 27 ]. Interestingly, the contents of total phenolic compounds of AR extract could reach the level of 5.52 mg GAE/g, which is unexpectedly much higher than that of aqueous extract of Ganoderma lucidum reported in other studies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has contributed to the global demand for mushrooms as food. Additionally, various cultivated mushrooms have been suggested as potent functional foods due to the biological properties of their componentsas shown using experimental models and clinical trials [26][27][28][29][30][31]. Considering the conditions under which cultivated mushrooms are obtained, one could assume that their quality-regarding the nutritional value and level of contamination-is superior to specimens collected from the wild.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, methanolic, ethyl acetate and aqueous (5 mg/mL) extracts of Pleurotus eous (pink oyster mushroom) showed significant anti-aggregatory effects upon stimulation with ADP (1 mM) in human isolated platelets by 45%, 35% and 36%, respectively [ 155 ]. Poniedziałek et al [ 156 ] studied the effect of the hot aqueous extract of eight edible mushrooms: Agaricus bisporus , Auricularia auricularia-judae , Coprinus comatus , Ganoderma lucidum , Hericium erinaceus , Lentinula edodes , Pleurotus eryngii and Pleurotus ostreatus in human whole blood platelet aggregation induced by 6.5 µM ADP. However, only P. eryngii , A. bisporus , A. auricularia-judae and C. comatus , showed significant inhibition effects, of 65.1%, 58.0%, 54.3%, and 51.6%, respectively.…”
Section: Edible Fungimentioning
confidence: 99%